Sistem Pengelolaan Daya Tarik Wisata Pulau Gili Ketapang Sebagai Aset Desa Gili Ketapang, Kecamatan Sumber Asih, Kabupaten Probolinggo - Dermawan, Decky Abdi; Anom, I Putu (JURNAL DESTINASI PARIWISATA, 2019)
Probolinggo is an area East Java which has beautiful tourism area, especially Gili Ketapang Island. This research purposes to know how the management system in Gili Ketapang Village Asset, Sumber Asih , Probolinggo Regency. The tourist attraction management system is an important indicator in determining the success of a tourist attraction, therefore the attraction of Gili Ketapang requires a good management system in order to become a leading attraction. Data collection techniques conducted in this study are observation techniques, unstructured interview techniques and documentary techniques. Determination technique of informant by using purposive sampling technique. Data analysis technique used is qualitative data. The conclusion of the discussion is the management system of Gili Ketapang tourist attraction on planning, organizing, actuating, and controlling, in each of the five components there are variables of tourism attraction, management and improvement of human resources, tourism facilities, service quality improvement, and promotion and marketing.On the other hand, this study also discusses what obstacles faced by government and society in the implementation of Gili Ketapang tourism management system.In knowing these obstacles required variables are physical constraints, among others, regarding parking, access, lodging, and shopping. Non-physical constraints on the social condition of the community, the condition of human resources, economic benefits, and institutions. Suggestions are addressed to the next Government, Manager, Society, and Academia in subsequent research Keywords: Management system, Tourist Attraction, and constraints.